Analysis of OFF-state and ON-state performance in a silicon-on-insulator power MOSFET with a low-k dielectric trench - 汪志刚 张波 李肇基 (Journal of semiconductors, 2013)
A novel silicon-on-insulator（SOI） MOSFET with a variable low-k dielectric trench（LDT MOSFET） is proposed and its performance and characteristics are investigated.The trench in the drift region between drain and source is filled with low-k dielectric to extend the effective drift region.At OFF state,the low-k dielectric trench（LDT） can sustain high voltage and enhance the dielectric field due to the accumulation of ionized charges. At the same time,the vertical dielectric field in the buried oxide can also be enhanced by these ionized charges. Additionally,ON-state analysis of LDT MOSFET demonstrates excellent forward characteristics,such as low gateto -drain charge density（〈 0.6 nC/mm~2） and a robust safe operating area（0-84 V）.